2019
DOI: 10.21608/svu.2019.23582
|View full text |Cite
|
Sign up to set email alerts
|

Nephro-Protective Effect of Wheat Germ Oil on Gentamicin-Induced Acute Nephrotoxicity in Wistar Albino Rat

Abstract: Gentamicin (GM) is an aminoglycoside antibiotic that possesses a wide range of anti-microbial activity. Currently, uses of gentamicin are narrowed due to it supposedly induces nephrotoxicity. Therefore, the aim of this study is to evaluate the possible nephron-protective effect of wheat germ oil (WGO), and its antioxidant potential against gentamicin-induced toxicity in Wistar albino rats. Forty rats were randomly assigned to four different groups (Ten animals each); Group I was administered normal saline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It has been reported that some symptoms of nephrotoxicity are present in up to 30 percent of patients treated with gentamicin for more than 7 days (3). Renal damage is often expressed by an increase in creatinine and urea nitrogen serum levels (4).…”
mentioning
confidence: 99%
“…It has been reported that some symptoms of nephrotoxicity are present in up to 30 percent of patients treated with gentamicin for more than 7 days (3). Renal damage is often expressed by an increase in creatinine and urea nitrogen serum levels (4).…”
mentioning
confidence: 99%
“…The wheat germ oil is the richest natural source of vitamin E (α-tocopherol) (Gerald et al, 2017). Hafez et al (2019) found that rats received 3g/kg wheat germ oil had a non-significant increase in Malondialdehyde (MDA) levels of serum at the 15 th day of study as compared to control group. Saleh (2016) found that oral administration of wheat germ oil (1400 mg⁄kg) to mice for eight days improved the liver and small intestine damage induced by carbon tetrachloride.…”
Section: Introductionmentioning
confidence: 99%